STUDI LITERATUR CASH WAQF CROWDFUNDING DI INDONESIA - Amin Al Jawi; Andri Soemitra (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2022)
This study aims to reveal the concepts and motives behind the phenomenon of the development of the crowdfunding platform which is currently booming in Indonesia, especially cash waqf crowdfunding. Literature study, content analysis and descriptive qualitative are the types and approaches used in this research. The results showed that cash waqf crowdfunding is a type of donation crowdfunding which in Islam is included in the Islamic philanthropic scheme in addition to zakat, infaq, alms and qurban. The motivation for the crowdfunding platform is the empowerment of the poor with the spirit and approach of religion, humanity (social) and culture (gotong royong, NKRI and Bhinneka Tunggal Ika). Then there are 8 wakif motivations in cash waqf which are clustered into 3 aspects/approaches, namely religious aspects/approaches, including: (i) religious religiosity/emotional, (ii) empathy altruism, (iii) human interest, (iv) platform credibility. Socio-cultural aspects/approaches include: (i) reinforcement or social influencers, (ii) the spirit of gotong royong and Bhinneka Tunggal Ika. As well as aspects/approaches of information technology, including: (i) performance expectations, (ii) effort expectations, and (iii) facilitating conditions.